Brucellosis - laboratory workers' nightmare come true: A case study - Lebogang Skosana; Farzana Ismail; Nontombi Mbelle; Mohamed Said (AOSIS, 2020)
Introduction: Brucella spp. are rarely encountered organisms in the medical microbiology laboratory and, when encountered, can cause concern in laboratory workers. Laboratory personnel may in fact develop serious disease as a result of this exposure. This case highlights shortcomings in recognition of Brucella spp. from a patient presenting atypically as well as the follow-up and management of an infected patient. Case presentation: The patient was an 8-year-old boy from a rural area of South Africa who presented to an academic hospital with a bladder mass and history of enuresis in September 2016. Brucella melitensis was isolated from a blood culture submitted to the laboratory. The child was subsequently treated for brucellosis in November 2016. Management and outcome: The source of infection in the patient was traced to consumption of unpasteurised milk from a local farmer. The patient was treated with doxycycline 100 mg twice daily and rifampicin 600 mg daily for 6 weeks and completed treatment, however he was not followed up at our hospital. The laboratory personnel, however, did not handle the specimen as a Biosafety Level 3 pathogen as this organism is not commonly encountered; they were provided with prophylaxis for brucellosis (rifampicin and doxycycline). Conclusion: Brucella spp. is a dangerous pathogen, easily capable of causing significant exposure in an unsuspecting and unprepared laboratory. The case discusses the management of brucellosis in the infected patient as well as the management of laboratory exposure to Brucella spp. Our case also describes the public health response to a case of brucellosis.